Retrofits of Residential Buildings to Slow the Climate Change - Bomberg, M.; Yarbrough, D.; Romanska-Zapala, A.; Kuc, S. (Current Advances in Geography, Environment and Earth Science Vol. 1, 2021)
Starting from the definition of net zero emission as the key to understanding climate change, this short overview article shows the reader that the only way to accelerate the green revolution is not through a focus on green materials, but through a broad public-private programs of education and demonstration about the need for reinvesting in the next generation of retrofitted buildings. To this end, re-thinking the way we retrofit residential buildings is necessary. A trend towards holistic design with integrated design process (IDP) introduced a different pattern of thinking that now has been reinforced by the need to modify ventilation and indoor air flow pattern to confine SAR-coV spread in habitable space. Thus, integrated control of heating, cooling air movement and humidity and leads to a merger of new technology with building automatics and open new horizons for environmental quality management in buildings. This essay deals with renovation of new building as this is a single, most important and easiest way to reduce carbon emissions.